Resonant enhancement of thermomagnetic convection of paramagnetic fluid in an enclosure due to time-periodic magnetizing force. (2nd July 2020) - He, Wenqiang; Qin, Guoliang; Wen, Xiaoping; Lin, Jingxiang; Jia, Cheng
Abstract: A numerical study is performed to demonstrate the thermomagnetic convection of air in a side-wall heated enclosure under constant gravity and time-periodic magnetizing force formed by current with sinusoidal waveform. Two cases have been considered: electric coil is located at the right side of the enclosure in case 1, and in case 2 the electric coil is below the enclosure. The spectral element method is applied to obtain the numerical solutions from the time-dependent Navier-Stokes equations including the magnetizing force term. The computed results show the existence of resonance, which is characterized by the maximum fluctuation of heat transfer in the interior. And the resonance phenomenon becomes more distinctive as Ra increases. Details of fluid flow and heat transfer under resonance is scrutinized by examining the evolution of oscillating components. The results indicate that case 1 exhibits advantages in using resonance to enhance the heat transfer rate, where a smaller magnetic strength is employed to simultaneously obtain larger fluctuations of fluid flow and heat transfer.